One-Pot Synthesis and Molecular Modeling Studies of New Bioactive Spiro-Oxindoles Based on Uracil Derivatives as SARS-CoV-2 Inhibitors Targeting RNA Polymerase and Spike Glycoprotein - Samar A. El-Kalyoubi; Ahmed Ragab; Ola A. Abu Ali; Yousry A. Ammar; Mohamed G. Seadawy; Aya Ahmed; Eman A. Fayed (MDPI AG, 2022)
The first outbreak in Wuhan, China, in December 2019 was reported about severe acute coronaviral syndrome 2 (SARS-CoV-2). The global coronavirus disease 2019 (COVID-19) pandemic in 2020 resulted in an extremely high potential for dissemination. No drugs are validated in large-scale studies for significant effectiveness in the clinical treatment of COVID-19 patients, despite the worsening trends of COVID-19. This study aims to design a simple and efficient cyclo-condensation reaction of 6-aminouracil derivatives 2a-e and isatin derivatives 1a-c to synthesize spiro-oxindoles 3a-d, 4a-e, and 5a-e. All compounds were tested in vitro against the SARS-CoV-2. Four spiro[indoline-3,5'-pyrido[2,3-d:6,5-d']dipyrimidine derivatives 3a, 4b, 4d, and 4e showed high activities against the SARS-CoV-2 in plaque reduction assay and were subjected to further RNA-dependent-RNA-polymerase (RdRp) and spike glycoprotein inhibition assay investigations. The four compounds exhibited potent inhibitory activity ranging from 40.23 ± 0.09 to 44.90 ± 0.08 nM and 40.27 ± 0.17 to 44.83 ± 0.16 nM, respectively, when compared with chloroquine as a reference standard, which showed 45 ± 0.02 and 45 ± 0.06 nM against RdRp and spike glycoprotein, respectively. The computational study involving the docking studies of the binding mode inside two proteins ((RdRp) (PDB: 6m71), and (SGp) (PDB: 6VXX)) and geometrical optimization used to generate some molecular parameters were performed for the most active hybrids.